Optimising rehabilitation and recovery after a stroke. Issue 6 (27th July 2022) - Bonifacio, Guendalina B; Ward, Nick S; Emsley, Hedley C A; Cooper, Jon; Bernhardt, Julie
Abstract : Stroke can cause significant disability and impact quality of life. Multidisciplinary neurorehabilitation that meets individual needs can help to optimise recovery. Rehabilitation is essential for best quality care but should start early, be ongoing and involve effective teamwork. We describe current stroke rehabilitation processes, from the hyperacute setting through to inpatient and community rehabilitation, to long-term care and report on which UK quality care standards are (or are not) being met. We also examine the gap between what stroke rehabilitation is recommended and what is being delivered, and suggest areas for further improvement.